Nutritional and Functional Status in Newly Hospitalized Older Patients Who are Not Underweight. Issue 2 (3rd July 2017) - Kańtoch, Anna; Wielek, Jolanta; Gryglewska, Barbara; Grodzicki, Tomasz
ABSTRACT: Although malnutrition is commonly associated with being underweight, it occurs whenever nutrient intakes are inadequate, regardless of current body weight. The aim of the study was to determine nutritional status as a predictor of functional status among older patients without underweight according to body mass index (BMI) at hospital admission. This cross-sectional study enrolled 90 patients aged ≥65 years (mean age 78.1 ± 6.4). Assessments included basic and Instrumental Activities of Daily Living (bADL, IADL), Mini Nutritional Assessment (MNA), and BMI. Most of respondents were at risk of malnutrition (46%) or malnutrition (17%) according to MNA. Patients with/at risk of malnutrition had lower scores in bADL ( p  = 0.020), IADL ( p  = 0.010) and MNA ( p  < 0.001). Scores for bADL and IADL positively correlated with MNA ( r  = 0.34, r  = 0.42, respectively) and negatively with age ( r  = −0.33, r  = −0.21). MNA scores were also significant predictors of staying independence in bADL ( β  = 0.53, p  < 0.001) and IADL ( β  = 0.45, p  < 0.001) in regression analysis. Our findings indicated that most older patients with normal/elevated BMI were malnourished or at risk of malnutrition and experienced functional limitations in ADL at admission to hospital. In this population, nutritional status estimated by MNA appears to be one of the most important factors in predicting functional status of older adults who are not underweight.